Síntese de nanocompósitos formados por polipirrol, nanomateriais de carbono e nanopartículas de prata em substrato de sílica para aplicação em dispositivos eletro-ópticos - Queiroz, Sophia Prado de (2023)
Materials on a nanometer scale are a recurring subject in science these days, because materials, when obtained on this size scale, begin to show variations in their properties, due to the large surface/volume ratio of the particles. The generated properties are exclusive, different from those of the formulated solid and the isolated atom, being related to the shape, size and medium where the particles are incorporated. Despite the interesting characteristics of these pure materials, a combination of two or more materials can present singularities due to the synergism between the forming parts, when there is this change in the characteristics of the nanomaterial, it is classified as a nanocomposite. The objective of this work is the synthesis of a nanocomposite formed by silver nanoparticles (AgNPs), polypyrrole and carbon nanotubes (CNTs), the nanomaterial being synthesized in a single step, in which the oxidative polymerization of the monomer (pyrrole) promotes the reduction of nanoparticles, the reaction being carried out in an aqueous medium with functionalized carbon nanotubes, in the middle, só that the CNTs supplemented encapsulated between the polymeric chains, this material is synthesized anchored on silica surfaces, observing the application in electro-optical devices, through optical fiber doping. Being the characterization of these materials done with absorption spectroscopy in the visible ultraviolet, since silver nanoparticles present plasmon absorption in the visible, changes can be created in the signal by the nanoparticles with the polymer, for the characterization of metallic nanoparticles, measurements of X-ray diffraction, transmission electron microscopy images make it possible to observe the size of nanoparticles and their shape and put an end to Raman spectroscopy that validates the presence of the polymer and CNTs.